Chapter: ''Sex and History': Talking Sex with Objects from the Past' from book: The Palgrave Handbook of Sexuality Education - Jen Grove (Palgrave Macmillan, 2017)
This chapter describes the 'Sex and History' project which uses objects from the past as the basis for discussions with young people about sexuality, as part of sexuality education. The chapter outlines key aspects of a methodology in which historical and cultural distance, coupled with striking familiarities in concerns about sex throughout history, bring contemporary expectations and norms into sharper focus and encourage young people to re-consider them critically. This chapter considers the different contexts within which this methodology can be applied and the challenges of trying to embed it into mainstream UK education. It describes how the project responds to international calls for a multidisciplinary approach to young people's healthy development and the importance of non-biological dimensions to sexuality education, such as consent, gender, body image and the impact of pornography.